3D-printed aerogels and solution-blow spun fibers modified with metal-organic framework/molybdenum disulfide for adsorption and photodegradation of environmental contaminants - Alves, Ana Laura Martins Mulkson (Universidade Federal de São Carlos, 2025)
3D-PRINTED AEROGELS AND SOLUTION-BLOW SPUN FIBERS MODIFIED WITH METAL-ORGANIC FRAMEWORK/MOLYBDENUM DISULFIDE FOR ADSORPTION AND PHOTODEGRADATION OF ENVIRONMENTAL CONTAMINANTS. The removal of organic contaminants from aqueous systems, such as synthetic dyes, poses a significant challenge due to the limited efficiency of conventional methods typically employed. The presence of dyes in the environment can lead to various negative impacts, as these compounds often exhibit toxicity and persistence. In this context, the development of novel and efficient methods and materials capable of not only removing but also degrading such contaminants is imperative. In this work, a material based on MOF (metal-organic framework) MIL-88A and MoS₂ was synthesized to develop an efficient photocatalyst for environmental contaminant removal. Photodegradation tests using methylene blue (MB) as a model dye, with the material in powder form, demonstrated an efficiency exceeding 90 % within 120 min. To facilitate reuse and minimize photocatalyst aggregation in solution, the MOF/MoS₂ was immobilized onto two distinct platforms: I) aerogels fabricated via 3D printing and ii) polyvinylpyrrolidone (PVP)/SiO₂ fibers produced by solution blow spinning (SBS). The 3D-printed aerogels were fabricated using gelatin, carboxymethylcellulose, and alginate, incorporating 5 % and 7.5 % by weight of MOF/MoS₂, and were designated as HD (without MOF/MoS₂), HD/MOF/MoS₂ 5 %, and HD/MOF/MoS₂ 7.5 %. Adsorption tests showed efficiencies of 16.77 %, 28.66 %, and 95.86 %, respectively. In photodegradation experiments, all aerogels achieved efficiencies exceeding 80 %. The PVP/SiO₂ fibers produced by SBS underwent thermal treatment to for partial removal of the polymeric portion before incorporating MOF/MoS₂. In MB removal tests using PVP/SiO₂/MOF/MoS₂ fibers, efficiencies greater than 90 % were observed within 48 h. Additionally, the PVP/SiO₂ fibers contributed to both adsorption and photodegradation processes, suggesting a synergistic effect. Finally, the PVP/SiO₂/MOF/MoS₂ platform demonstrated versatility in removal other dyes and the antibiotic tetracycline. Thus, the results obtained for both platforms indicate their potential for mitigating environmental contaminants.
Impressão 3D de aerogeis e fibras fiadas por sopro de solução, modificadas com estruturas metal-orgânicas/dissulfeto de molibdênio para adsorção e fotodegradação de contaminantes ambientais
Keywords: Impressão 3D; Polímeros naturais; Aerogel; Contaminantes orgânicos; Fotocatálise; Fiação por sopro de solução; Fibras de PVP/SiO2; Remediação ambiental; 3D printing; Natural polymers; Photocatalysis; Organic contaminants; Solution-blow spinning; PVP/SiO2 fibers; Environmental remediation; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA